Effect of maturity status on lower-limb strength testing reliability in academy football players from an elite professional club - Maxime Violin; Abd-elbasset Abaïdia; Guillaume Rave; Sébastien Ratel (Current Issues in Sport Science)
Introduction: In top-level football, clubs seek to identify young talent. This identification requires using tests to notably evaluate the lower-limb strength, which is a decisive physical quality in football performance. However, the tests used are not always highly reliable to interpret results meaningfully, particularly among age categories since their reliability could differ according to maturity status (Ferrari et al., 2023). In addition, lower-limb strength testing reliability may also vary according to movements performed, whether these are mono- or poly-articular. In this sense, it is possible to suggest that pre-pubertal players exhibit lower scores of test-retest reliability during poly-articular movements than their older counterparts because of their poorer motor coordination due to immaturity of cerebellum. However, this remains to be further clarified. Therefore, the aim of this study was to examine the test-retest reliability of dominant lower-limb strength on abduction, adduction, anterior or posterior chain movements in football players from an elite professional club academy, and to compare the results depending on maturity status and movement performed. Our hypothesis is that strength testing reliability will be lower for pre-pubertal than pubertal and post-pubertal players, more particularly for poly- than mono-articular movements in pre-pubertal players.